Copy number variant discrepancy resolution using the ClinGen dosage sensitivity map results in updated clinical interpretations in ClinVar. Issue 11 (11th October 2018) - Riggs, Erin R.; Nelson, Tristan; Merz, Andrew; Ackley, Todd; Bunke, Brian; Collins, Christin D.; Collinson, Morag N.; Fan, Yao‐Shan; Goodenberger, McKinsey L.; Golden, Denae M.; Haglund‐Hazy, Linda; Krgovic, Danijela; et al.
Abstract: Conflict resolution in genomic variant interpretation is a critical step toward improving patient care. Evaluating interpretation discrepancies in copy number variants (CNVs) typically involves assessing overlapping genomic content with focus on genes/regions that may be subject to dosage sensitivity (haploinsufficiency (HI) and/or triplosensitivity (TS)). CNVs containing dosage sensitive genes/regions are generally interpreted as "likely pathogenic" (LP) or "pathogenic" (P), and CNVs involving the same known dosage sensitive gene(s) should receive the same clinical interpretation. We compared the Clinical Genome Resource (ClinGen) Dosage Map, a publicly available resource documenting known HI and TS genes/regions, against germline, clinical CNV interpretations within the ClinVar database. We identified 251 CNVs overlapping known dosage sensitive genes/regions but not classified as LP or P; these were sent back to their original submitting laboratories for re‐evaluation. Of 246 CNVs re‐evaluated, an updated clinical classification was warranted in 157 cases (63.8%); no change was made to the current classification in 79 cases (32.1%); and 10 cases (4.1%) resulted in other types of updates to ClinVar records. This effort will add curated interpretation data into the public domain and allow laboratories to focus attention on more complex discrepancies. Abstract : The ClinGen Dosage Sensitivity (DS) Map provides evidence‐based assessments of the haploinsufficiency and triplosensitivity of genes/genomic regions. We identified 251 clinical copy number variants (CNVs) in ClinVar that overlapped known DS genes/regions but were not interpreted as "likely pathogenic" or "pathogenic;" these were sent back to their original laboratories for re‐evaluation. Of the 246 that were re‐evaluated, 63.0% resulted in updated classifications, showing that the ClinGen DS Map can be an effective initial step in CNV classification discrepancy resolution.